Paintings, Drawings, and Prints by Paul Klee : From the Klee Foundation, Berne, Switzerland with Additions from American Collections - Klee, Paul (Museum of Modern Art)
Catálogo de la exposición homónima, presentada en el MOMA de Nueva York, en 1949.